Interest rates and the spatial polarization of housing markets - Francisco Osswald do Amaral; Martin Dohmen; Sebastian Kohl; Moritz Schularick (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Rising within-country differences in house values are a much debated trend in the U.S. and internationally. Using new long-run regional data for 15 advanced economies, we first show that standard explanations linking growing price dispersion to rent dispersion are contradicted by an important stylized fact: rent dispersion has increased far less than price dispersion. We then propose a new explanation: a uniform decline in real risk-free interest rates can have heterogeneous spatial effects on house values. Falling real safe rates disproportionately push up prices in large agglomerations where initial rent-price ratios are low, leading to housing market polarization on the national level.
Keywords: G10; G12; G51; R30; 330; House prices; regional housing markets; spatial polarization